Optimalisasi Gerakan Literasi Sekolah dalam Persiapan Asesmen Nasional - Lidya Amalia Rahmania (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: There is a change in National Examination into National Assessment that gives a different challenge for the teachers and students. The instrument of National Assessment has three components: (1) Minimum Competency Assessment, (2) Character Survey, and (3) Academic Environment Survey. To aim the maximum marks on National Assessment, the students should have a high literacy skill. It could be achieved using the School Literacy Movement (GLS). The research used literature study using secondary data. The analysis used descriptive method systematically and critically. Conceptually, the School Literacy Movement (GLS) would be a great way to help the students improve their literacy skill and develop their critical minds. However, practically there are many schools that have difficulties in implementing the School Literacy Movement. There are three obstacles that hindering the implementation of School Literacy Movement: (1) Facilities and infrastructures, (2) Bureaucracy, and (3) Human Resources. Those obstacles could be solved with the change of the mindset to optimize the School Literacy Movement: (1) Motivation, (2) Instant Gratification, (3) Observation, (4) Novelty, (5) Analytical and Critical Thinking, and (6) Freedom of Choices. The change of mindset is needed to enhance the effectivity and efficiency of the School Literacy Movement so that the facilitators and the students could improve their literacy skill for National Assessment in the near future, and to improve the character of the people of Indonesia in the future. Keywords: School Literacy Movement, national assessment, GLS Optimalization Abstrak: Perubahan format Ujian Nasional menjadi Asesmen Nasional memberikan tantangan tersendiri terhadap para guru dan siswa. Instrumen AN memiliki 3 aspek: (1) Asesmen Kompetensi Minimum (AKM), (2) Survei Karakter, dan (3) Survei Lingkungan Belajar. Untuk mencapai nilai AKM yang maksimal, siswa harus memiliki tingkat literasi yang tinggi. Hal itu dapat dicapai dengan menggunakan Gerakan Literasi Sekolah (GLS). Penelitian dilakukan dengan metode studi literatur menggunakan data sekunder. Proses analisis secara deskriptif dilakukan setelah data yang diperoleh, dikaji secara mendalam, dengan urutan yang sistematis, dan kritis. Secara konsep, GLS akan sangat membantu siswa dalam meningkatkan kemampuan literasi dan sikap kritis siswa. Akan tetapi, secara praktik masih banyak sekolah yang kesulitan untuk memaksimalkan GLS dengan baik. Beberapa jenis kendala yang dialami oleh sekolah yaitu: (1) Kendala sarana dan prasarana, (2) Kendala birokratis, dan (3) Kendala sumber daya manusia. Kendala-kendala tersebut dapat diselesaikan dengan beberapa perubahan paradigma berpikir untuk optimalisasi GLS yang telah diusulkan, yaitu: (1) Motivasi, (2) Gratifikasi Instan, (3) Observasi, (4) Kebaruan, (5) Pembiasaan Sikap Analitis, dan (6) Pemberian Kebebasan. Dengan adanya perubahan paradigma berpikir ini diharapkan para fasilitator dan siswa dapat meningkatkan literasi dan karakternya agar berhasil menempuh AN dalam jangka pendek, dan menguatkan karakter moral bangsa dalam jangka panjang. Kata kunci: Gerakan Literasi Sekolah, asesmen nasional, optimalisasi GLS